TPE (thermoplastic elastomer) composite material for automobile foot mat and preparation method of TPE composite material
The TPE composite material for automobile floor mats addresses bacterial accumulation and UV degradation issues by incorporating modified titanium dioxide, offering enhanced durability, antibacterial properties, and personalized design.
Patent Information
- Application Number
- CN202510467399.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2025-07-15
AI Technical Summary
Existing car foot pads are prone to accumulate bacteria during use, resulting in a decrease in air quality, poor UV aging resistance, short service life, single color and pattern, and cannot achieve personalized design.
Using TPE composite material, the softened bottom blister plate and pre-set three-dimensional plate are blistered on the blister mold with negative pressure blister mold, combined with modified nanotitanium dioxide, the multi-color and multi-patterned personalized effect is achieved, and the material is given excellent tensile performance, UV aging resistance and antibacterial properties.
It realizes the personalized design of multi-color and multi-patterned car foot pads, improves antibacterial performance and UV aging resistance, extends service life, and is environmentally friendly and convenient.
Smart Images

Figure BDA0005358905330000101 
Figure BDA0005358905330000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of automotive floor mats, and particularly relates to a TPE composite material for automotive floor mats and a preparation method thereof. Background Art
[0002] With the popularization of automobiles, automotive floor mats have become indispensable consumer goods. At the same time, due to the improvement of people's living standards, people have more and more requirements for automotive floor mats. Automotive floor mats not only belong to interior decorations, playing a role in beautifying, comfort and embellishment, but also can effectively prevent stains from directly falling on the inner bottom of the car. However, after long-term use, a large amount of bacteria will accumulate on the floor mat, which will cause a significant decline in the air quality inside the car. Especially in winter, the outdoor temperature is relatively low, and generally the car windows will be closed tightly, which will lead to a closed environment inside the car. Coupled with a large number of bacteria on the floor mat, it will pose a threat to the health of people inside the car. Moreover, over time, the automotive floor mat will age due to the long-term influence of temperature and ultraviolet rays, thus reducing the service life of the floor mat. In addition, the existing automotive floor mat products have a single color, do not match the color of the car interior, and cannot achieve the presentation of personalized colors. Moreover, the surface pattern of the product is single and cannot flexibly present a variety of patterns. Summary of the Invention
[0003] To solve the deficiencies mentioned in the above background art, the purpose of the present invention is to provide a TPE composite material for automotive floor mats and a preparation method thereof. By moving the softened bottom layer thermoformed sheet to the thermoforming mold for negative pressure thermoforming and fusing it with the pre-set three-dimensional sheet at the same time, the personalized effect of multiple colors or multiple patterns can be achieved. In addition, modified nano-titanium dioxide is added to the pre-set three-dimensional material to endow it with excellent tensile properties, ultraviolet aging resistance, heat resistance and antibacterial properties.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A TPE composite material for automotive floor mats includes a bottom layer thermoforming material and a pre-set three-dimensional material fused on the surface of the bottom layer thermoforming material. The pre-set three-dimensional material includes the following components in parts by weight: 40-60 parts of SEBS elastomer, 10-20 parts of low-density polyethylene, 5-15 parts of EVA resin, 5-10 parts of modified nano-titanium dioxide, 1-6 parts of lubricant, 8-15 parts of plasticizer, and 1-5 parts of color masterbatch;
[0006] The modified nano-titanium dioxide is prepared by grafting a modified additive onto the surface of nano-titanium dioxide; the modified additive is prepared by subjecting a functional additive and 2-(2,4-dihydroxyphenyl)-2H-benzotriazole to a substitution reaction with a modified antibacterial monomer; the functional additive is prepared by subjecting a component obtained by hydrogen reduction of 2-cyano-6-hydroxybenzothiazole under the action of Raney-Ni to an acylation reaction with 5-methylisoxazole-3-carbonyl chloride; the modified antibacterial monomer is prepared by subjecting an antibacterial monomer obtained by a Schiff base reaction of benzothiazole-2-carbaldehyde and 2,6-dichloro-4-aminophenol to a substitution reaction with 3-chloropropyltriethoxysilane.
[0007] Preferably, the bottom blister material comprises the following components in parts by weight: 40-70 parts of SEBS elastomer, 10-25 parts of polypropylene, 8-15 parts of inorganic filler, 1-6 parts of lubricant, 10-15 parts of plasticizer; the inorganic filler is one or a combination of nano-silica, nano-titanium dioxide, mica particles, vermiculite, carbon nanotubes, montmorillonite, nano-calcium carbonate.
[0008] Preferably, the lubricant is one or a combination of stearic acid, polyethylene wax, oxidized polyethylene wax, paraffin wax; the plasticizer is paraffin base white oil.
[0009] Preferably, the preparation of the modified nano-titanium dioxide comprises the following steps:
[0010] A. Take 2-cyano-6-hydroxybenzothiazole in a reactor, add ethanol and stir to mix, then add Raney-Ni, and stir the obtained mixture at room temperature for 3-4 h under a hydrogen pressure of 0.3-0.4 MPa. After the reaction is completed, filter and concentrate to obtain component one. Take 5-methylisoxazole-3-carbonyl chloride and dissolve it in anhydrous dichloromethane, add triethylamine and component one, and stir and react for 10-12 h. After the reaction is completed, concentrate under vacuum and purify by column chromatography to prepare the functional additive;
[0011] B. Take benzothiazole-2-carbaldehyde and 2,6-dichloro-4-aminophenol in a reactor, add methanol and stir to mix, reflux at 60-70 °C for 3-5 h, and after the reaction is completed, filter, wash and dry to prepare the antibacterial monomer;
[0012] C. Take the antibacterial monomer, 3-chloropropyltriethoxysilane, triethylamine and tetrahydrofuran in a reactor, stir and react at 60-75 °C in a nitrogen atmosphere for 4-6 h. After the reaction is completed, filter with suction, wash and dry to prepare the modified antibacterial monomer;
[0013] D. Take a functional additive, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, and triethylamine in a reactor, add a mixed solution of a modified antibacterial monomer and tetrahydrofuran, place it at 60-75 °C and stir for reaction for 5-8 h. After the reaction is completed, filter, wash, and dry to prepare a modified additive;
[0014] E. Ultrasonically disperse nano-titanium dioxide in a mixed solution of absolute ethanol and deionized water, then add the modified additive, place it at 55-70 °C and stir for reaction for 4-7 h. After the reaction is completed, centrifuge, wash, and dry to prepare modified nano-titanium dioxide.
[0015] Preferably, in step A, the molar ratio of 2-cyano-6-hydroxybenzothiazole to 5-methylisoxazole-3-carbonyl chloride is 1:1-1.1.
[0016] Preferably, in step B, the molar ratio of benzothiazole-2-carbaldehyde to 2,6-dichloro-4-aminophenol is 1-1.2:1.
[0017] Preferably, in step C, the molar ratio of the antibacterial monomer to 3-chloropropyltriethoxysilane is 1:1-1.2.
[0018] Preferably, in step D, the molar ratio of the functional additive, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, and the modified antibacterial monomer is 1-1.1:1-1.1:1.
[0019] A preparation method of a TPE composite material for an automotive floor mat, comprising the following steps:
[0020] S1. Weigh each component by weight, take SEBS elastomer and polypropylene and premix them in a mixer, then add an inorganic filler, a lubricant, and a plasticizer, and place it at 75-90 °C to mix evenly to obtain a bottom-layer thermoforming material;
[0021] S2. Weigh each component by weight, take SEBS elastomer, low-density polyethylene, and EVA resin and premix them in a mixer, then add modified nano-titanium dioxide, a lubricant, a plasticizer, and a masterbatch, and place it at 75-90 °C to mix evenly to obtain a preformed three-dimensional material;
[0022] S3. Extrude and pelletize the bottom-layer thermoforming material and the preformed three-dimensional material respectively through a twin-screw extruder, and then extrude them into a bottom-layer thermoforming sheet and a preformed three-dimensional sheet respectively at 190-220 °C through a single-screw extruder;
[0023] S4. Cut the prefabricated three-dimensional sheet material into a set shape, place it in the groove of the thermoforming mold, then heat and soften the bottom thermoforming sheet material and move it to the position of the thermoforming mold for negative pressure thermoforming. The thermoforming negative pressure is 0.02 - 0.06 kPa to fuse the bottom thermoforming sheet material and the prefabricated three-dimensional sheet material, and prepare the TPE composite material for automotive floor mats.
[0024] Preferably, the softening temperature of the bottom thermoforming sheet material is 30 - 70 °C higher than that of the prefabricated three-dimensional sheet material.
[0025] Advantages of the present invention:
[0026] The present invention uses 2-cyano-6-hydroxybenzothiazole to undergo hydrogen reduction under the action of a Raney-Ni catalyst to catalyze the hydrogenation of the cyano group to generate a primary amine (-CH2NH2), and prepares Component 1. Then, Component 1 and 5-methylisoxazole-3-carbonyl chloride undergo an acylation reaction to prepare a functional additive, thereby introducing both a benzothiazole group with antibacterial activity and an oxazole group with high heat resistance into the structure of the functional additive. At the same time, the present invention uses the aldehyde group in benzothiazole-2-carboxaldehyde to react with the amino group in 2,6-dichloro-4-aminophenol to prepare an antibacterial monomer containing an antibacterial Schiff base group and an antibacterial benzothiazole group. Then, the hydroxyl group in the antibacterial monomer undergoes a substitution reaction with the chlorine atom in 3-chloropropyltriethoxysilane to prepare a modified antibacterial monomer. Subsequently, the hydroxyl group in the functional additive and the hydroxyl group in the 2-(2,4-dihydroxyphenyl)-2H-benzotriazole structure respectively undergo substitution reactions with the two chlorine atoms in the modified antibacterial monomer to prepare a modified additive, thereby further introducing a benzotriazole group with ultraviolet absorption function into the structure of the modified additive. Then, the silanol groups introduced in the modified additive and the hydroxyl groups on the surface of nano-titanium dioxide undergo a condensation reaction to prepare modified nano-titanium dioxide, thereby endowing the material with excellent ultraviolet aging resistance, antibacterial, and heat resistance effects. Among them, nano-titanium dioxide, as a commonly used inorganic ultraviolet shielding agent, can cooperate with the benzotriazole group introduced in the modified additive to resist ultraviolet aging. Moreover, the modified additive is firmly bonded to the surface of nano-titanium dioxide through chemical bonds, which can endow the material with long-term ultraviolet aging resistance, antibacterial, and heat resistance effects. In addition, the grafting of the modified additive is beneficial to the relatively uniform dispersion of nano-titanium dioxide in the matrix material, enabling the comprehensive performance of nano-titanium dioxide to be fully exerted.
[0027] The present invention cuts and shapes pre-set three-dimensional plates with different colors or patterns, and then pre-sets them onto a thermoforming mold by means of inlaying as the three-dimensional colored plates on the surface of an automotive floor mat for later use. Then, while moving the softened bottom thermoformed plate onto the thermoforming mold for negative-pressure thermoforming, it is fused with the pre-set three-dimensional plate, so as to present the pre-set three-dimensional plates with different colors or patterns on the main surface of the automotive floor mat, thereby achieving a personalized effect of multiple colors or multiple patterns. Moreover, during the fusion process of the bottom thermoformed plate and the pre-set three-dimensional plate, no glue is required for bonding, which is more environmentally friendly and convenient. Detailed implementation mode
[0028] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0029] Embodiment 1 A modified nano-titanium dioxide includes the following steps:
[0030] A. Take 1.7 g of 2-cyano-6-hydroxybenzothiazole in a reactor, add 50 mL of ethanol and stir to mix, then add 0.1 g of Raney-Ni. The obtained mixture is stirred at room temperature for 4 h under a hydrogen pressure of 0.3 MPa. After the reaction is completed, it is filtered and concentrated to obtain Component 1. Take 1.5 g of 5-methylisoxazole-3-carbonyl chloride and dissolve it in 100 mL of anhydrous dichloromethane, add 1 g of triethylamine and Component 1, and stir and react for 12 h. After the reaction is completed, it is vacuum concentrated and purified by a chromatography column to prepare a functional additive;
[0031] B. Take 1.7 g of benzothiazole-2-carboxaldehyde and 1.8 g of 2,6-dichloro-4-aminophenol in a reactor, add 100 mL of methanol and stir to mix, and reflux and react at 65 °C for 4 h. After the reaction is completed, it is filtered, washed, and dried to prepare an antibacterial monomer;
[0032] C. Take 3.2 g of antibacterial monomer (Mr = 323.2), 2.6 g of 3-chloropropyltriethoxysilane, 1 g of triethylamine, and 100 mL of tetrahydrofuran in a reactor, and stir and react at 70 °C for 5 h in a nitrogen atmosphere. After the reaction is completed, it is filtered, washed, and dried to prepare a modified antibacterial monomer;
[0033] D. Take 2.9 g of the functional additive (Mr = 289.2), 2.3 g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, and 2 g of triethylamine in a reactor. Add a mixed solution of 5.2 g of the modified antibacterial monomer (Mr = 527.5) and 120 mL of tetrahydrofuran, and stir and react at 70 °C for 6 h. After the reaction is completed, filter by suction, wash, and dry to prepare the modified additive;
[0034] E. Take 5 g of nano-titanium dioxide and ultrasonically disperse it in a mixed solution of 90 mL of absolute ethanol and 10 mL of deionized water. Then add 3.5 g of the modified additive, and stir and react at 65 °C for 5 h. After the reaction is completed, centrifuge, wash, and dry to prepare the modified nano-titanium dioxide.
[0035] Example 2 A bottom blister material comprises the following components in parts by weight: 42 parts of SEBS elastomer, 11 parts of polypropylene, 8 parts of nano-silica, 2 parts of lubricant stearic acid, and 10 parts of plasticizer paraffin-based white oil;
[0036] A preformed three-dimensional material comprises the following components in parts by weight: 44 parts of SEBS elastomer, 12 parts of low-density polyethylene, 5 parts of EVA resin, 6 parts of the modified nano-titanium dioxide prepared in Example 1, 2 parts of lubricant stearic acid, 10 parts of plasticizer paraffin-based white oil, and 1.5 parts of masterbatch.
[0037] The preparation method of the above-mentioned TPE composite material for automotive floor mats comprises the following steps:
[0038] S1. Weigh each component according to the parts by weight. Take the SEBS elastomer and polypropylene and put them into a mixer for premixing. Then add nano-silica, lubricant, and plasticizer, and mix evenly at 80 °C to obtain the bottom blister material;
[0039] S2. Weigh each component according to the parts by weight. Take the SEBS elastomer, low-density polyethylene, and EVA resin and put them into a mixer for premixing. Then add the modified nano-titanium dioxide, lubricant, plasticizer, and masterbatch, and mix evenly at 80 °C to obtain the preformed three-dimensional material;
[0040] S3. Extrude and pelletize the bottom blister material and the preformed three-dimensional material respectively through a twin-screw extruder, and then extrude them into bottom blister plates and preformed three-dimensional plates respectively at 205 °C through a single-screw extruder;
[0041] S4. Cut the preformed three-dimensional plate into a set shape, place it in the groove of the blister mold, and then heat and soften the bottom blister plate and move it to the position of the blister mold for negative pressure blistering. The blistering negative pressure is 0.05 kPa to fuse the bottom blister plate and the preformed three-dimensional plate to prepare the TPE composite material for automotive floor mats.
[0042] Example 3 A bottom blister material comprises the following components in parts by weight: 51 parts of SEBS elastomer, 15 parts of polypropylene, 12 parts of nano-silica, 3.5 parts of lubricant polyethylene wax, and 12 parts of plasticizer paraffin-based white oil;
[0043] A prefabricated three-dimensional material comprises the following components in parts by weight: 50 parts of SEBS elastomer, 16 parts of low-density polyethylene, 7 parts of EVA resin, 7.5 parts of the modified nano-titanium dioxide prepared in Example 1, 4 parts of lubricant polyethylene wax, 12 parts of plasticizer paraffin-based white oil, and 2 parts of masterbatch.
[0044] The preparation method of the above-mentioned TPE composite material for automotive floor mats is the same as that in Example 2.
[0045] Example 4 A bottom blister material comprises the following components in parts by weight: 66 parts of SEBS elastomer, 23 parts of polypropylene, 14 parts of nano-silica, 5 parts of lubricant oxidized polyethylene wax, and 14 parts of plasticizer paraffin-based white oil;
[0046] A prefabricated three-dimensional material comprises the following components in parts by weight: 57 parts of SEBS elastomer, 18 parts of low-density polyethylene, 11 parts of EVA resin, 9 parts of the modified nano-titanium dioxide prepared in Example 1, 5 parts of lubricant oxidized polyethylene wax, 13 parts of plasticizer paraffin-based white oil, and 4 parts of masterbatch.
[0047] The preparation method of the above-mentioned TPE composite material for automotive floor mats is the same as that in Example 2.
[0048] Comparative Example 1 A modified nano-titanium dioxide comprises the following steps:
[0049] A. Take 1.7 g of 2-cyano-6-hydroxybenzothiazole in a reactor, add 50 mL of ethanol and stir to mix, then add 0.1 g of Raney-Ni. The obtained mixture is stirred at room temperature for 4 h under a hydrogen pressure of 0.3 MPa. After the reaction is completed, it is filtered and concentrated to obtain Component 1. Take 1.5 g of 5-methylisoxazole-3-carbonyl chloride and dissolve it in 100 mL of anhydrous dichloromethane, add 1 g of triethylamine and Component 1, and stir and react for 12 h. After the reaction is completed, it is concentrated under vacuum and purified by a chromatography column to prepare a functional additive;
[0050] B. Take 1.7 g of benzothiazole-2-carboxaldehyde and 1.8 g of 2,6-dichloro-4-aminophenol in a reactor, add 100 mL of methanol and stir to mix, and reflux at 65 °C for 4 h. After the reaction is completed, it is filtered, washed, and dried to prepare an antibacterial monomer;
[0051] C. Take 3.2 g of the antibacterial monomer (Mr = 323.2), 2.6 g of 3-chloropropyltriethoxysilane, 1 g of triethylamine, and 100 mL of tetrahydrofuran in a reactor. Stir and react at 70 °C for 5 h under a nitrogen atmosphere. After the reaction is completed, filter, wash, and dry to prepare a modified antibacterial monomer.
[0052] D. Take 2.9 g of the functional additive (Mr = 289.2) and 1 g of triethylamine in a reactor. Add a mixed solution of 5.2 g of the modified antibacterial monomer (Mr = 527.5) and 120 mL of tetrahydrofuran. Stir and react at 70 °C for 6 h. After the reaction is completed, filter, wash, and dry to prepare a modified additive.
[0053] E. Take 5 g of nano-titanium dioxide and ultrasonically disperse it in a mixed solution of 90 mL of absolute ethanol and 10 mL of deionized water. Then add 3.5 g of the modified additive. Stir and react at 65 °C for 5 h. After the reaction is completed, centrifuge, wash, and dry to prepare a modified nano-titanium dioxide.
[0054] Comparative Example 2 A modified nano-titanium dioxide comprises the following steps:
[0055] A. Take 1.7 g of benzothiazole-2-carboxaldehyde and 1.8 g of 2,6-dichloro-4-aminophenol in a reactor. Add 100 mL of methanol and stir to mix. Reflux and react at 65 °C for 4 h. After the reaction is completed, filter, wash, and dry to prepare an antibacterial monomer.
[0056] B. Take 3.2 g of the antibacterial monomer (Mr = 323.2), 2.6 g of 3-chloropropyltriethoxysilane, 1 g of triethylamine, and 100 mL of tetrahydrofuran in a reactor. Stir and react at 70 °C for 5 h under a nitrogen atmosphere. After the reaction is completed, filter, wash, and dry to prepare a modified antibacterial monomer.
[0057] C. Take 2.3 g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and 1 g of triethylamine in a reactor. Add a mixed solution of 5.2 g of the modified antibacterial monomer (Mr = 527.5) and 120 mL of tetrahydrofuran. Stir and react at 70 °C for 6 h. After the reaction is completed, filter, wash, and dry to prepare a modified additive.
[0058] D. Take 5 g of nano-titanium dioxide and ultrasonically disperse it in a mixed solution of 90 mL of absolute ethanol and 10 mL of deionized water. Then add 3.5 g of the modified additive. Stir and react at 65 °C for 5 h. After the reaction is completed, centrifuge, wash, and dry to prepare a modified nano-titanium dioxide.
[0059] Comparative Example 3 A bottom blister material comprises the following components in parts by weight: 66 parts of SEBS elastomer, 23 parts of polypropylene, 14 parts of nano-silica, 5 parts of lubricant oxidized polyethylene wax, and 14 parts of plasticizer paraffin-based white oil;
[0060] A prefabricated three-dimensional material comprises the following components in parts by weight: 57 parts of SEBS elastomer, 18 parts of low-density polyethylene, 11 parts of EVA resin, 9 parts of modified nano-titanium dioxide prepared in Comparative Example 1, 5 parts of lubricant oxidized polyethylene wax, 13 parts of plasticizer paraffin-based white oil, and 4 parts of masterbatch.
[0061] The preparation method of the above-mentioned TPE composite material for automotive floor mats is the same as that in Example 2.
[0062] Comparative Example 4 A bottom blister material comprises the following components in parts by weight: 66 parts of SEBS elastomer, 23 parts of polypropylene, 14 parts of nano-silica, 5 parts of lubricant oxidized polyethylene wax, and 14 parts of plasticizer paraffin-based white oil;
[0063] A prefabricated three-dimensional material comprises the following components in parts by weight: 57 parts of SEBS elastomer, 18 parts of low-density polyethylene, 11 parts of EVA resin, 9 parts of modified nano-titanium dioxide prepared in Comparative Example 2, 5 parts of lubricant oxidized polyethylene wax, 13 parts of plasticizer paraffin-based white oil, and 4 parts of masterbatch.
[0064] The preparation method of the above-mentioned TPE composite material for automotive floor mats is the same as that in Example 2.
[0065] Comparative Example 5 A bottom blister material comprises the following components in parts by weight: 66 parts of SEBS elastomer, 23 parts of polypropylene, 14 parts of nano-silica, 5 parts of lubricant oxidized polyethylene wax, and 14 parts of plasticizer paraffin-based white oil;
[0066] A prefabricated three-dimensional material comprises the following components in parts by weight: 57 parts of SEBS elastomer, 18 parts of low-density polyethylene, 11 parts of EVA resin, 9 parts of nano-titanium dioxide, 5 parts of lubricant oxidized polyethylene wax, 13 parts of plasticizer paraffin-based white oil, and 4 parts of masterbatch.
[0067] The preparation method of the above-mentioned TPE composite material for automotive floor mats is the same as that in Example 2.
[0068] Performance testing
[0069] The prefabricated three-dimensional materials prepared in Examples 2-4 and Comparative Examples 3-5 were made into test samples with the specifications of 100 mm×6.5 mm×3 mm for performance testing: the tensile performance was tested using a universal mechanical testing machine with reference to the standard of GB / T 1040.2-2022; and the samples were placed in an aging oven and subjected to ultraviolet aging for 10 h and 24 h under a 1000W mercury lamp to test the change rate of tensile strength and evaluate the ultraviolet aging resistance of the samples; the samples were placed in a TGA-103 thermogravimetric analyzer, and under nitrogen protection, the temperature was raised from room temperature to 800℃ at a heating rate of 5℃ / min, and the initial decomposition temperature of the material was recorded to evaluate the heat resistance of the samples; the suspensions of Staphylococcus aureus and Escherichia coli with a concentration of 10 7 CFU / mL were smeared on the surface of the prefabricated three-dimensional material, covered with a sterile PE film, and after standing for 1 h, the prefabricated three-dimensional material was rinsed with phosphate buffer solution. The rinsing solution was smeared on the culture medium and cultured for 24 h to count the number of colonies, and the antibacterial rate was calculated to evaluate the antibacterial performance of the samples. The data results are shown in Table 1.
[0070] Table 1 Test Results of Specimen Performance
[0071]
[0072]
[0073] It can be seen from the data in Table 1 that the materials prepared in Examples 2-4 of the present invention have excellent tensile performance, ultraviolet aging resistance, heat resistance and antibacterial performance. Among them, the modified nano-titanium dioxide component added in Comparative Example 3 did not introduce benzotriazole groups, and the change rates of tensile strength at 10 h and 24 h were significantly different from those in Examples 2-4, indicating that the grafting of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole can improve the ultraviolet aging resistance of the material. The modified nano-titanium dioxide component added in Comparative Example 4 was not grafted with functional additives, and the measured initial thermal decomposition temperature, Escherichia coli inhibition rate and Staphylococcus aureus inhibition rate of the material were lower than those in Examples 2-4, indicating that the grafting of functional additives can improve the heat resistance and antibacterial performance of the material. In Comparative Example 5, the nano-titanium dioxide was not modified, and its measured ultraviolet aging resistance, heat resistance and antibacterial performance were lower than those in Examples 2-4, and the measured tensile strength and elongation at break were also lower than those in Examples 2-4. The possible reason is that the agglomeration of nano-titanium dioxide leads to a decrease in mechanical properties, and the Escherichia coli inhibition rate and Staphylococcus aureus inhibition rate were further lower than those in Comparative Example 4, indicating that the grafting of antibacterial monomers can further improve the antibacterial performance of the material.
[0074] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0075] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and the descriptions in the specification only illustrate the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed.
Claims
1. A TPE composite material for automotive floor mats, characterized in that, It includes a bottom plastic-absorbing material and a pre-set three-dimensional material fused on the surface of the bottom plastic-absorbing material. The pre-set three-dimensional material includes the following components in parts by weight: 40-60 parts of SEBS elastomer, 10-20 parts of low-density polyethylene, 5-15 parts of EVA resin, 5-10 parts of modified nano-titanium dioxide, 1-6 parts of lubricant, 8-15 parts of plasticizer, and 1-5 parts of masterbatch; The modified nano-titanium dioxide is made by grafting a modified additive onto the surface of nano-titanium dioxide; among them, the modified additive is made by simultaneously substituting a functional additive and 2-(2,4-dihydroxyphenyl)-2H-benzotriazole with a modified antibacterial monomer; among them, the functional additive is made by acylating component one obtained by hydrogen reduction of 2-cyano-6-hydroxybenzothiazole under the action of Raney-Ni with 5-methylisoxazole-3-carbonyl chloride; the modified antibacterial monomer is made by substituting the antibacterial monomer obtained by the Schiff base reaction of benzothiazole-2-carbaldehyde and 2,6-dichloro-4-aminophenol with 3-chloropropyltriethoxysilane.
2. The TPE composite material for automotive floor mats according to claim 1, wherein The bottom plastic-absorbing material includes the following components in parts by weight: 40-70 parts of SEBS elastomer, 10-25 parts of polypropylene, 8-15 parts of inorganic filler, 1-6 parts of lubricant, and 10-15 parts of plasticizer; the inorganic filler is one or a combination of nano-silica, nano-titanium dioxide, mica particles, vermiculite, carbon nanotubes, montmorillonite, and nano-calcium carbonate.
3. The TPE composite material for automotive floor mats according to claim 1 or 2, characterized in that, The lubricant is one or a combination of stearic acid, polyethylene wax, oxidized polyethylene wax, and paraffin wax; the plasticizer is paraffin-based white oil.
4. The TPE composite material for automotive floor mats according to claim 1, wherein, The preparation of the modified nano-titanium dioxide includes the following steps: A. Take 2-cyano-6-hydroxybenzothiazole in a reactor, add ethanol and stir to mix, then add Raney-Ni. The obtained mixture is stirred at room temperature for 3-4 h under a hydrogen pressure of 0.3-0.4 MPa. After the reaction is completed, it is filtered and concentrated to obtain component one. Take 5-methylisoxazole-3-carbonyl chloride and dissolve it in anhydrous dichloromethane, add triethylamine and component one, and stir and react for 10-12 h. After the reaction is completed, it is concentrated under vacuum and purified by a chromatography column to prepare a functional additive; B. Take benzothiazole-2-carbaldehyde and 2,6-dichloro-4-aminophenol in a reactor, add methanol and stir to mix, and reflux at 60-70 °C for 3-5 h. After the reaction is completed, it is filtered, washed, and dried to prepare an antibacterial monomer; C. Take the antibacterial monomer, 3-chloropropyltriethoxysilane, triethylamine, and tetrahydrofuran in a reactor, and stir and react at 60-75 °C in a nitrogen atmosphere for 4-6 h. After the reaction is completed, it is filtered, washed, and dried to prepare a modified antibacterial monomer; D. Take the functional additive, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, and triethylamine in a reactor, add a mixed solution of the modified antibacterial monomer and tetrahydrofuran, and stir and react at 60-75 °C for 5-8 h. After the reaction is completed, it is filtered, washed, and dried to prepare a modified additive; E. Ultrasonically disperse nano-titanium dioxide in a mixed solution of absolute ethanol and deionized water, then add a modification additive, place it at 55 - 70 °C and stir for reaction for 4 - 7 h. After the reaction is completed, centrifuge, wash, and dry to prepare modified nano-titanium dioxide.
5. The TPE composite material for automotive floor mats according to claim 4, wherein, In the step A, the molar ratio of 2-cyano-6-hydroxybenzothiazole to 5-methylisoxazole-3-carbonyl chloride is 1:1 - 1.
1.
6. The TPE composite material for automotive floor mats according to claim 4, characterized in that, In the step B, the molar ratio of benzothiazole-2-carboxaldehyde to 2,6-dichloro-4-aminophenol is 1 - 1.2:
1.
7. The TPE composite material for automotive floor mats according to claim 4, wherein In the step C, the molar ratio of the antibacterial monomer to 3-chloropropyltriethoxysilane is 1:1 - 1.
2.
8. The TPE composite material for automotive floor mats according to claim 4, wherein, In the step D, the molar ratio of the functional additive, 2-(2,4-dihydroxyphenyl)-2H-benzotriazole, and the modified antibacterial monomer is 1 - 1.1:1 - 1.1:
1.
9. A preparation method of the TPE composite material for automotive floor mats according to claim 2, characterized in that, Comprising the following steps: S1. Weigh each component by weight. Take SEBS elastomer and polypropylene and put them into a mixer for premixing, then add inorganic filler, lubricant, and plasticizer, and place it at 75 - 90 °C to mix evenly to obtain the bottom-layer thermoforming material. S2. Weigh each component by weight. Take SEBS elastomer, low-density polyethylene, and EVA resin and put them into a mixer for premixing, then add modified nano-titanium dioxide, lubricant, plasticizer, and masterbatch, and place it at 75 - 90 °C to mix evenly to obtain the preformed three-dimensional material. S3. Extrude and pelletize the bottom-layer thermoforming material and the preformed three-dimensional material respectively through a twin-screw extruder, and then extrude them into the bottom-layer thermoforming sheet and the preformed three-dimensional sheet respectively at 190 - 220 °C through a single-screw extruder. S4. Cut the preformed three-dimensional sheet into a set shape, place it in the groove of the thermoforming mold, then heat and soften the bottom-layer thermoforming sheet and move it to the position of the thermoforming mold for negative-pressure thermoforming. The thermoforming negative pressure is 0.02 - 0.06 kPa, and fuse the bottom-layer thermoforming sheet and the preformed three-dimensional sheet to prepare the TPE composite material for automotive floor mats.
10. The preparation method of the TPE composite material for automotive foot pads according to claim 9, characterized in that, The softening temperature of the bottom-layer thermoforming sheet is 30 - 70 °C higher than that of the preformed three-dimensional sheet.
Citation Information
Cited By
Anti-ultraviolet epoxy resin coating and preparation method thereof
CN120944429A
An anti-ultraviolet epoxy resin coating and its preparation method
CN120944429B